2018
DOI: 10.2217/epi-2018-0080
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of microfibrillar-associated proteins reveals MFAP4 as a novel biomarker in human cancers

Abstract: This integrated analysis provides new insights into MFAPs in human cancers and indicates that MFAP4 could be used as novel biomarker for developing therapies against human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…In the present study, CSRP1 was downregulated in ACC, which indicated that CSRP1 may be a tumor suppressor gene. MFAP4 is a tumor suppressor gene in prostate cancer and it displays low expression in breast cancer (29,30). By contrast, downregulated MFAP4 may lead to adverse clinical incidents in ovarian cancer (31).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, CSRP1 was downregulated in ACC, which indicated that CSRP1 may be a tumor suppressor gene. MFAP4 is a tumor suppressor gene in prostate cancer and it displays low expression in breast cancer (29,30). By contrast, downregulated MFAP4 may lead to adverse clinical incidents in ovarian cancer (31).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, copy number variant (CNV) analysis in 464 individuals identified MFAP4 as a candidate gene for the severe cardiac malformations associated with left-sided congenital heart disease (LS-CHD) 2 . More recently, numerous studies have implicated MFAP4 as a prognostic marker (or biomarker) for assorted cancers, including ovarian 3 , 4 , mammary 5 and prostate 6 , as well as hepatic and pulmonary fibrosis 7 and chronic obstructive pulmonary disease (COPD) 8 . Despite the growing list of diseases that implicate MFAP4 in their aetiology, the exact function of MFAP4 in vivo remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when the Euclidean distance and the Manhattan distance were used to characterize tumor similarity, we found that the high-grade tumors were more dissimilar to each other than the low-grade tumors (Additional file 1: Table S6). Among them was PSA (KLK3), and several other well established PCa-associated proteins like AGR2 [36], MDH2 [37], MFAP4 [38] and FABP5 [39]. We observed that for some of these top 20 proteins,…”
Section: Resultsmentioning
confidence: 87%